The first decade of using multiphoton microscopy for high-power kidney imaging - Peti-Peterdi, János (American Physiological Society, 2012)
In this review, we highlight the major scientific breakthroughs in kidney research achieved using multiphoton microscopy (MPM) and summarize the milestones in the technological development of kidney MPM during the past 10 years. Since more and more renal laboratories invest in MPM worldwide, we discuss future directions and provide practical, useful tips and examples for the application of this still-emerging optical sectioning technology. Advantages of using MPM in various kidney preparations that range from freshly dissected individual glomeruli or the whole kidney in vitro to MPM of the intact mouse and rat kidney in vivo are reviewed. Potential combinations of MPM with micromanipulation techniques including microperfusion and micropuncture are also included. However, we emphasize the most advanced and complex, quantitative in vivo imaging applications as the ultimate use of MPM since the true mandate of this technology is to look inside intact organs in live animals and humans.